Desain Tempat Penyimpanan Sementara (TPS) Limbah B3 sesuai Regulasi PP 22 Tahun 2021 Dan PerMen LHK No. 6 Tahun 2021 bagi Industri Rokok - Imroatul Khumaidah; Nurfa Anisa; Nanta Sigit (Science: Indonesian Journal of Science, 2025)
The tobacco industry is one of the manufacturing sectors that generates hazardous and toxic waste (B3) from various production, maintenance, and utility support activities. This waste exhibits hazardous and toxic characteristics. In practice, some tobacco industries have established Temporary Storage Facilities (TPS) for B3 waste; however, not all comply with the technical requirements stipulated by current regulations. This study aims to design a TPS for B3 waste that aligns with Government Regulation No. 22 of 2021 and Ministry of Environment and Forestry Regulation No. 6 of 2021. The research methods include literature review, direct observation of two existing TPS, and the design of a new TPS for an industry that does not yet have such a facility. The results show that the hazardous waste generated in the tobacco industry includes flammable liquids, flammable solids, corrosive substances, environmentally hazardous materials, and toxic substances. Based on the analysis, the proposed TPS has an area of 18.55 m² with a capacity of 55.65 m³, and is equipped with packaging facilities consisting of three iron drums (100 liters), two HDPE plastic containers (100 liters), and one jumbo bag (200 liters). Additional design elements include 7.09 m² of ventilation area, a spill channel measuring 0.2 m × 0.25 m, and a storage tank of 0.4 m × 0.4 m × 0.4 m. Supporting facilities comprise one unit of a 6 kg fire extinguisher, one unit of sink/eyewash station, Personal Protective Equipment (PPE), and one first aid kit.